Jeux interdits Forbidden games / Janus Films ; Studio Canal ; Silver-Films présente une production de Robert Dorfmann ; adaptation cinematographique, Jean Aurenche, Pierre Bost, René Clément ; un film de René Clément ; dialogues, Pierre Bost, Jean Aurenche, François Boyer. - Clément, René, 1913-1996.; Fossey, Brigitte.; Poujouly, Georges, 1940-2000.; Dorfmann, Robert, 1912-1999.; Aurenche, Jean.; Bost, Pierre, 1901-; Boyer, François, 1920-2003.; Yepes, Narciso.; Boyer, François, 1920-2003. (Janus Films : Criterion Collection [distributor], 2006)
A timeless evocation of the loss of innocence, Rene Clement's devastating Forbidden games tells the story of a young orphan and her friend forced to fend for themselves in World War II France.